Underlying Factors of the Use of E-Commerce by SMEs in Tanjung Lesung - Rofian Almas Akbar; Adhi Setyo Santoso; Andi Ina Yustina; Hajanirina Andrianantenaina (International Journal of Applied Business and International Management, 2022)
This study aims to analyze the factors that the SME onwers in Tanjung Lesung need to promote their products through e-commerce. This study employed a quantitative method, presenting 23 questions anticipated to provide insight into the research problem. This study purposively selected 300 samples of small and medium-sized business owners who use the internet to sell their products. The results show that the management relationship between productivity and actual behavior revealed a favorable relationship between perceived usefulness and actual behavior, but a negative relationship between external pressure on actual behavior and organizational support for actual behavior. The study's limitations included the impact of internet usage via e-commerce on small and medium-sized businesses. Keywords: Actual Behavior, External Pressure, Managerial Productivity, Organizational Support, Perceived Usefulness